Flavonoid Levels and Antioxidant Capacity of Mulberry Leaves: Effects of Growth Period and Drying Methods - Hu, Lei; Wang, Cheng; Guo, Xiang; Chen, Dekui; Zhou, Wei; Chen, Xiaoyang; Zhang, Qing (Frontiers in Plant Science, 2021)
In recent years, various mulberry leaf dishes have gradually gained in popularity. The harvesting period of mulberry leaves, and the preparation of dried samples, are critical for the retention of flavonoid content and activity. In this study, changes in flavonoid levels in mulberry leaves during their growth period (3–6 months), and the effects of four different drying methods (sun drying (SD), air drying (AD), oven drying (OD), and freeze drying (FD)) on flavonoid accumulation and antioxidant capacity, were determined. The results showed that mulberry leaves grown for 6 months had higher levels of flavonoids, and different drying methods could significantly affect the flavonoid levels and antioxidant capacity of the leaves. Air drying and FD were the best methods in terms of retaining the antioxidant activity of flavonoids, although AD had lower operating costs than FD in the production process. Therefore, to obtain a high flavonoid content and maximum antioxidant activity, AD is recommended for mulberry leaves.